Determinants of Profit Growth of PT. Bank BCA Syariah - Dewi, Suvina Dewi; Ulya, Zikriatul Ulya; Hisan, Khairatun Hisan (Journal Research of Economic and Bussiness, 2024)
The Sharia banking sector has an important role in economic growth and plays a role in maintaining liquidity to support a country's economic activities. Thus, sharia banking can create more stable domestic economic conditions by improving its financial performance. Good bank financial performance is very necessary for bank operations to function well. This research aims to analyze how banks can create more stable economic conditions in the country by improving their financial performance. Good bank financial performance is very important so that the bank can function well. This research aims to analyze the influence of return on equity (ROE), capital adequacy ratio (CAR) and non-performing loan financing (NPF) on income growth for the 2012-2022 period. The data used in this research is secondary data and the method used is quantitative research, namely multiple linear regression analysis of time series data with the help of the Eviews 9 software program. The population in this research is PT Bank BCA Syariah for the 2012-2022 period, the sample used is 44 quarterly data. The research results show that return on equity (ROE) has a significant influence on Profit Growth with a value of Tcount > Ttable (-3.974466 > 1.68385) and a significant value of 0.00 < 0.05. ), Capital Adequacy Ratio (CAR) has no effect and is not significant on Profit Growth, the T value is -0.922161 < T table 1.68385 and the significant value is 0.36 > 0.05. Non-Performing Financing (NPF) has a significant and significant effect on Profit Growth, the t value is 3.450257 > t table 1.68385 and the significant value is 0.00 < 0.05. Return on equity (ROE), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) have a significant and significant effect on Profit Growth with a value of Fcount > Ftable (19.78459 > 2.84) and a significant value of 0.00 < 0 .05 means the size of the increase or decrease in ROE, CAR, and NPF on Profit Growth.